Prevention and Correction of Motivation for Illegal Behavior of Minors - Yu. Blyasova, I.; A. Klayberg, Yu.; A. Malyushina, Yu.; Ð. Kokanov, N.; Yu. Lushnikova, T. (International Journal of Engineering and Technology, 2018)
The relevance of the research based on the necessity of studying the components of criminal motivation of minors and their psychological content. In this regard, this article is aimed at identifying the components of criminal motivation, prevention and correction with the help of a correctional-developing training program "Quartet". The leading approaches (or methods) of the study of this problem are the systematic approach, methods of mathematical statistics, which allows to develop and carry out prevention and correction of criminal motivation. The article presents the results of the trainings with minors, the main concepts of criminal motivation are revealed. The analysis of the differences between the parameters of the psychological content of the components of the motivational sphere of the personality of the juvenile offender (individual, personal, cognitive, emotional and behavioral) of the U. Student’s t-criterion showed that there are reliable positive changes in the structure of the motivational sphere of the personality of the minor offender. In the control group of minors, there was no change, according to it, we can conclude that the motivation for illegal behavior of minors can be corrected by means of socio-psychological training through awareness and influence on the psychological content of the components of the structure of the motivational sphere and changes in the hierarchy of leading motives. The materials of the article are of practical value. Research materials can be used in professional activities of investigators, juvenile inspectors, social rehabilitation centers dealing with juvenile offenders. They are applicable in dealing with educators, psychologists, and employees of law enforcement agencies for advisory and educational purposes. The technique "Dominant criminal motive" can be used both in individual work with juvenile offenders and for monitoring the state of juvenile delinquency. The correctional-developing training program â€œQuartetâ€ developed by the author can be used to change the motivational sphere of the personality of juvenile offenders, the formation of adequate behavior of minors, and to carry out measures to prevent the relapses committed by minors. The reliability of the research results, its conclusions and recommendations is provided by the methodology and logic of the research. Â Â